Fluorescent aminal linked porous organic polymer for reversible iodine capture and sensing - Sabri, Muhammad Ashraf (2020)
A novel triazene-anthracene-based fuorescent aminal linked porous organic polymer (TALPOP) was prepared via metal free-Schif base polycondensation reaction of 9,10-bis-(4,6-diamino-S-triazin2-yl)anthracene and 2-furaldehyde. The polymer has exceptional chemical and thermal stabilities and exhibit good porosity with Brunauer–Emmett–Teller surface area of 401 m2 g−1. The combination of such porosity along with the highly conjugated heteroatom-rich framework enabled the polymer to exhibit exceptional iodine vapor uptake of up to 314 wt % and reversible iodine adsorption in solution. Because of the inclusion of the anthracene moieties, the TALPOP exhibited excellent detection sensitivity towards iodine via forescence quenching with Ksv value of 2.9 × 103 L mol−1. The cost effective TALPOP along with its high uptake and sensing of iodine, make it an ideal material for environmental remediation.